PENGARUH PROMOSI PENJUALAN TERHADAP MINAT BELI ES KRIM BASKIN ROBBINS - Prayogi Prayogi; Aulia Januar Malik (SMART Management Journal, 2022)
This study aims to determine and analyze the effect of promotion on consumer interest in buying in PT. Trans Ice Baskin Robbins cabang Transmart Juanda Bekasi. The sampling technique was determined based on the Slovin formula by distributing questionnaires to the consumer of methods used are descriptive analysis method, statistical analysis method consisting of linearity analysis, and partial significant test (t-test). The research data were analyzed based on the theory of Gozali and Sugiyono and were then processed using SPSS 23.0. from the data tested, it was found that partial promotion has a positive and significant effect on consumer interest in buying. Indicated by a significant value of t of 0.001 smaller than 0.005 (0.001